ChemInform Abstract: Li2Ca2Si2O7: Structural, Spectroscopic and Computational Studies on a Sorosilicate. Issue 14 (April 2015) - Kahlenberg, Volker; Brunello, Emanuele; Hejny, Clivia; Krueger, Hannes; Schmidmair, Daniela; Tribus, Martina; Toebbens, Daniel M.
Abstract: Single crystals of the title compound are prepared from stoichiometric mixtures of Li2 CO3, CaCO3, and SiO2 (Pt crucible, 900 °C, 12 h).